Cardiometabolic Risk, Socio-Psychological Factors, and Trajectory of Grip Strength Among Older Japanese Adults. (October 2015) - Botoseneanu, Anda; Bennett, Joan M.; Nyquist, Linda; Shinkai, Shoji; Fujiwara, Yoshinori; Yoshida, Hiroto; Aiello, Allison; Cigolle, Christine T.; Liang, Jersey
Objective: To examine the association between cardiometabolic risk (percent body fat [BF%], triglycerides [TG], high-density lipoprotein [HDL]-cholesterol, hemoglobin A1c [HbA1c]), socio-psychological factors (education and self-rated health [SRH]), and trajectories of grip strength (GS) in older adults.Method: Longitudinal 8-year data from 1, 381 Japanese adults aged 65 years or above were analyzed using hierarchical linear models, stratified according to gender.Results: GS declined following a linear trajectory. In both genders, higher BF% was associated with weaker GS, but not with the rate of decline. GS trajectory did not correlate with baseline TG, HDL-C, or HbA1c. Cardiometabolic factors mediated educational differences in GS intercept in both genders. In women, better SRH predicted stronger GS. The effect of SRH was robust to adjustments for cardiometabolic risk.Discussion: In older adults, GS and its rate of decline are selectively associated with both cardiometabolic risk and socio-psychological characteristics. Cardiometabolic risk mediates educational disparities in GS but not differences in subjective assessments of health.